A photon thermal diode - Chen, Zhen; Wong, Carlaton; Lubner, Sean; Yee, Shannon; Miller, John; Jang, Wanyoung; Hardin, Corey; Fong, Anthony; Garay, Javier E.; Dames, Chris (Nature communications, 2014)
A thermal diode is a two-terminal nonlinear device that rectifies energy carriers (for example, photons, phonons and electrons) in the thermal domain, the heat transfer analogue to the familiar electrical diode. Effective thermal rectifiers could have an impact on diverse applications ranging from heat engines to refrigeration, thermal regulation of buildings and thermal logic. However, experimental demonstrations have lagged far behind theoretical proposals. Here we present the first experimental results for a photon thermal diode. The device is based on asymmetric scattering of ballistic energy carriers by pyramidal reflectors. Recent theoretical work has predicted that this ballistic mechanism also requires a nonlinearity in order to yield asymmetric thermal transport, a requirement of all thermal diodes arising from the second Law of Thermodynamics, and realized here using an ‘inelastic thermal collimator’ element. Experiments confirm both effects: with pyramids and collimator the thermal rectification is 10.9±0.8%, while without the collimator no rectification is detectable (<0.3%). A thermal diode is the heat transfer analogue of an electrical diode: it favours the flow of energy carriers such as photons, phonons or electrons in one direction. Here, the authors demonstrate a photon thermal diode that uses pyramidal reflectors to asymmetrically scatter the photons.